Impact of Media Influence on Advertising Revenue - with Reference to Dainik Bhaskar and Nai Dunia - Singh, A.K.; Singh, Mili (Indian Journal of Marketing, 2004)
In the next Century, media will be no longer be measured in just space and time but in other dimensions: Exposer, Emotions in attitude, understanding and Environment". Rupert Murdoch (1998). Advertising involves some uncertainty and risk. Have you picked the right target markets? Do you really understand what your customer’s want/ will the right people read the newspaper that carries your ads? Are your ads having any effect on the sales? Advertisers and their agencies face questions like these day after day. Newspapers are a major force in advertising, especially among local retailers, national franchises, and a diverse group of advertisers seeking a regional or local audience. Newspapers are among the most creditable of the mass media, and they are a source of information, entertainment, and advertising for millions of households each day. As advertisers increasingly include some regional and/or local strategy in their advertising plans, newspapers face growing competition in an area where they have long been dominant. In the most dramatic development (for newspapers, television passed newspapers in terms of overall advertising revenue to become the leading advertising medium. At the same time while the newspapers are fighting a battle to gain a respectable share of the national advertising rupee: they face a growing competition from the media. Even classified advertising, longs for the profitable mainstay of the newspaper industry; and is nervous over the potential for on-line services offering similar information.